Analisis Literatur tentang Peran Literasi Perpajakan dalam Meningkatkan Kepatuhan Wajib Pajak di Kota Tangerang Selatan - Adila Najwa; Elvrida Elisabeth; Andriansyah; Rudi Sanjaya (Jurnal Riset Multidisiplin Edukasi, 2026)
Tax literacy plays a strategic role in shaping taxpayer compliance behavior, particularly in areas with high economic complexity such as South Tangerang City. This study uses a Systematic Literature Review (SLR) approach to analyze the relationship between tax literacy and taxpayer compliance, based on eight primary studies and twenty-six supporting references focused on the South Tangerang context. Regional tax realization data from 2021 to 2024, sourced from the South Tangerang City Statistics Agency (BPS), serves as empirical evidence to support the findings. The literature synthesis consistently shows that tax literacy, which encompasses a substantive understanding of tax regulations, digital literacy in using the e-filing system, and awareness of tax obligations as citizens, has a positive and significant impact on taxpayer compliance. This finding applies to individual taxpayers, corporate taxpayers, and MSMEs in South Tangerang City. The growth in regional tax realization from IDR 1.52 trillion in 2021 to IDR 2.09 trillion in 2024 reflects an improving compliance trend. However, a gap remains between potential and realization, indicating the need for a more structured tax education program. This study concludes that improving tax literacy through accessible, digital-based education should be a policy priority for the South Tangerang City Government.